Beta-Endorphin and Serotonin Levels in Individuals with Methamphetamine use Disorder - Talib, Noor H.; Majeed , Maysaa J.; Hussein, Maher M. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Alterations in the levels of beta-endorphins and serotonin are heavily involved in the mood dysregulation regularly observed in individuals with methamphetamine use disorder, with lower levels of these neurotransmitters contributing to mood disturbances commonly seen in addiction. Such neurochemical imbalances may also disrupt normal mood regulation pathways, leading to the emotional and psychological challenges often experienced by individuals struggling with addiction. Objective: To investigate the relationship between beta-endorphin and serotonin levels in individuals with methamphetamine addiction, and to evaluate their potential roles in mood regulation and addiction-related behaviors. Methods: This observational study assessed the serum levels of beta-endorphin and serotonin in individuals with methamphetamine use disorder compared to healthy controls. Fifty patients with confirmed methamphetamine use disorder and fifty matched healthy individuals were recruited. ELISA (Enzyme-linked immunosorbent assay) was used to measure serum serotonin and beta-endorphin levels. Research permission was obtained with ethical approval from the Health Research Ethics Committee. Results: The results showed significantly lower levels of both neurotransmitters in the addiction group with mean ± SD (11.84 ± 3.64) of beta endorphin and means of 10.28 ± 3.21, of serotonin. A strong positive correlation between serotonin and beta-endorphin was also noted. These findings suggest a critical role of these neurochemicals in the mood disturbances associated with methamphetamine addiction. Conclusion: Mood regulation and addictive behaviors in methamphetamine addiction were impacted by changes in beta-endorphin and serotonin levels. Understanding these neurochemical changes help to develop more effective treatments for changes in mood and addictive behaviors.